Cardiovascular Protective Effect of Garcinia dulcis Flower Acetone Extract in 2-Kidney-1-Clip Hypertensive Rats - Nattaya Thongsepee; Pongsakorn Martviset; Wanwisa Himakhun; Pathanin Chantree; Phornphan Sornchuer; Kant Sangpairoj; Siriphun Hiranyachattada (Advances in Pharmacological and Pharmaceutical Sciences)
Morelloflavone and camboginol are bioactive compounds purified from Garcinia dulcis (GD), which has anti-inflammatory and antihypertensive properties. The objective of this study was to examine the cardiovascular protective effect of GD flower acetone extract in 2-kidney-1-clip (2K1C) hypertensive rats. Male Wistar rats underwent 2K1C or sham operation (SO) and were housed for 4 weeks. Each group of rats, then, was further divided into 2 subgroups receiving oral administration of either 50 mg/kg BW GD extract or corn oil (vehicle) daily for 4 weeks. Noninvasive blood pressure (BP) and body weight were measured weekly throughout the study. Subsequently, the invasive measurement of arterial BP and the heart rate were determined in all anesthetized rats. The baroreceptor reflex sensitivity (BRS) was investigated by injection of either phenylephrine or sodium nitroprusside for bradycardia or tachycardia response, respectively. Histological examination of the heart and thoracic aorta was also performed in order to investigate the general morphology and the tumor necrosis factor alpha (TNF-α) expression. We found that the GD flower extract significantly diminished the BP and restored the impaired BRS. Moreover, it also decreased the TNF-α expression in the cardiac muscle and thoracic aorta of 2K1C when compared to the SO group. Taken together, our data showed that GD flower extract exhibits the cardiovascular protective effect in the 2K1C hypertensive rats.